PENINGKATAN HASIL BELAJAR PADA TEMA KARAKTERISTIK GEOGRAFIS INDONESIA DI KELAS V SEKOLAH DASAR MENGGUNAKAN MODEL MIND MAPPING - Bayu Purbha Sakti (Program Studi PGSD Universitas Flores, 2020)
The teacher still uses the conventional learning model even though the fifth grade private primary school teacher in Bayat has implemented the 2013 curriculum. The implementation of learning carried out in the classroom is still one way where the teacher is the learning center while the students only record what the teacher says. The material to be studied is the theme of Indonesia's geographic characteristics because this theme is taught in fifth grade. Mind mapping learning model is a learning model used by students to be able to be creative in producing ideas or thoughts and noting what must be learned. This study used a classroom action research model of Kemmis & McTaggart. This study uses two cycles. Data analysis obtained from evaluation, interview, and observation. The use of the mind map learning model is proven to improve learning outcomes in the theme of Indonesia's geographic characteristics in grade V students in private elementary schools. The private primary school chosen is SD Kanisius Bayat. The learning outcomes obtained in the first cycle were the average value increased to 73.8 and were included in the criteria for 68.2%. The learning outcomes obtained in the second cycle increased again to 82.3 in the high criteria with a percentage of 100%. Improved material learning outcomes in Indonesia's geographic characteristics because teachers use the mind mapping model.